ACTH-PRODUCING PERIPHERAL PULMONARY CARCINOID - I. Z. Korobkova; D. A. Dremin; S. M. Kacalov; I. V. Kirsan; A. A. Ugrimov; S. A. Zubkova; A. O. Vas’kin; T. R. Alekseeva (Вестник рентгенологии и радиологии)
The paper describes a clinical example of the topical diagnosis of adrenocorticotropic hormone (ACTH)-producing typical peripheral pulmonary carcinoid. The first stage in its diagnosis was to rule out the production of ACTH by the pituitary gland. The paper presents information on the most common localization of functioning neuroendocrine tumors, as well as a diagnostic algorithm to search for an ectopic focus of the ACTH-secreting tumor that causes hypercorticism. Taking into account that bronchopulmonary neuroendocrine tumors with ectopic hormone production occur rarely (5%), a clinical example is given to demonstrate the capabilities of imaging techniques and standards for their implementation using an integrated approach.